Empowering Coastal Women Tourism Business Actors Based on Bank Indonesia's Go Digital Application in Kupang City - Manafe, Mesri Welhelmina Nisriani; Seseli, Eka Merdekawati Imelda; Kase, Marce Sherly; Fanggidae, Herny Constantia; Mbate, Maromi Merlin (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Student-based community service for female coastal culinary entrepreneurs in the tourism sector at Warna Beach, Kupang City is carried out because economically they are the group of business actors most vulnerable to the impact of Covid 19. This service activity aims to provide solutions based on situation analysis through socialization, training, and mentoring. e-financing, e-Payment, e-commerce, Go Digital Bank Indonesia in order to maintain the sustainability of MSMEs and in the long term it is hoped that it can encourage sustainable marine tourism. The method used is Participatory Action Research (PAR). The output target is to increase the knowledge and skills of 16 tourism business partners in using digital applications so that they are able to compete on a local scale. This service activity supports the achievement of main work indicators with a focus on serving the MBKM era on the use of digital technology, sustainability of the green economy, and encouraging the revival of the tourism sector. The achievement of this activity is that 16 partners have been able to carry out digital financial management using the SI APIK application. 16 Partners already have Facebook accounts, WA for business, Grab food, and Open Warung. These accounts have been used to conduct online marketing for each partner. Achieved 50% use of non-cash payments due to problems with several unbanked partners.